Spectrum of UGT1A1 Variations in Chinese Patients with Crigler-Najjar Syndrome Type II. - Lufeng Li; Guohong Deng; Yi Tang; Qing Mao (PLoS ONE, 2015)
Crigler-Najjar Syndrome type II (CNS-II) is an autosomal recessive hereditary condition of unconjugated hyperbilirubinemia without hemolysis, with bilirubin levels ranging from 102.6 μmol/L to 342 μmol/L. CNS-II is caused by a deficiency of UDP-glucuronyl transferase (UGT), which is encoded by the UDP-glucuronyl transferase 1A1 gene (UGT1A1). In East Asian populations, the compound homozygous UGT1A1 G71R and Y486D variants are frequently observed in cases with bilirubin levels exceeding 200 μmol/L. In this study, we investigated the spectrum of UGT1A1 variations in Chinese CNS-II patients. We sequenced the enhancer, promoter, and coding regions of UGT1A1 in 11 unrelated Chinese CNS-II patients and 80 healthy controls. Nine of these patients carried variations that are here reported for the first time in CNS-II patients, although they have been previously reported for other types of hereditary unconjugated hyperbilirubinemia. These individual variations have less influence on UGT activity than do the compound homozygous variation (combination of homozygous G71R variant and Y486D variant). Therefore, we propose that the spectrum of UGT1A1 variations in CNS-II differs according to the bilirubin levels.